Prevalence, incidence, and re-occurrence risk of musculoskeletal pain in older adults in the United Kingdom: a population-based study - Radojčić, Maja R.; Perera, Romain S.; Hart, Deborah J.; Spector, Tim D.; Arden, Nigel K. (Frontiers in Pain Research, 2023)
Background Throughout the literature pain burden has been assessed via different questions, often cross-sectionally. We know little about pain re-occurrence and how to translate knowledge between pain questions within the population of interest. We aimed to estimate the burden of musculoskeletal pain by estimating prevalence, incidence rates, and re-occurrence risk of back, hand, hip, knee, and foot pain using different questions from UK population-based samples and predict the number of affected individuals in 2030 in the UK.Methods We used two UK population-representative studies, two eight-year-apart follow-ups, and two pain questions assessing recent pain episodes and often troubled pain when walking.We estimated prevalence, 8-year incidence rates and 8-year pain re-occurrence risk for women and men aged 50 years and older and the relation between the two pain questions.Among UK individuals older than 50 years, musculoskeletal pain episode prevalence was 20-50% and incidence 20-40/1,000 person-years, while pain when walking prevalence was 10-25% and incidence 6-12/1,000 person-years. The most prevalent were back and knee pain; of 5 women experiencing back or knee pain episodes 3 are expected to be often troubled by pain. Hip and foot pain had similar estimates in both questions. Hand pain peaked in women aged 50-65 years. Women had higher prevalence and incidence rates, but men had a higher eight-year re-occurrence risk of all musculoskeletal pain types. Reporting a pain episode was associated with 2 times higher risk, but often troubled pain when walking with 4-7 times higher risk of the same pain in eight years. Women and men with BMI27kg/m 2 were twice as likely to experience musculoskeletal pain. In 2030, we expect 2-7 million people older than 50 years in the UK to seek site-specific musculoskeletal pain-focused health care.In individuals older than 50 years, the experience of musculoskeletal pain at least doubles the chance of experiencing it again. Women report musculoskeletal pain more often, but men report more persistent pain. Musculoskeletal pain presents a significant burden to public health.